The Analysis of Phenylbutazone and Its Active Metabolite, Oxyphenbutazone, in Equine Tissues (Muscle, Kidney, and Liver), Urine, and Serum by LC-MS/MS. (22nd November 2019) - Boison, Joe O; Dowling, Patricia; Matus, Johanna L; Kinar, Jana; Johnson, Ron
Abstract: This study reports the use of two validated LC with tandem MS (MS/MS) methods to study the residue depletion profile of phenylbutazone (PBZ) and its metabolite oxyphenbutazone (OXPBZ) from equine serum, urine, and muscle, kidney, and liver tissues. One LC-MS/MS method, with an LOQ of 1.0 ng/mL for PBZ and 2.0 ng/mL for OXPBZ, was used for the analysis of the two drugs in the biological fluids (equine urine and serum); the other LC-MS/MS method, with an LOQ of 0.5 ng/g for PBZ and OXPBZ, was used for the analysis of the drugs in the equine tissue samples. PBZ was administered intravenously to two horses dosed with 8.8 mg/kg PBZ once daily for 4 days and sacrificed humanely at a slaughter plant 7 days after the last drug administration. Urine, serum, and kidney, liver, and muscle tissues were collected from the two horses and shipped on ice to the laboratory and stored at −20°C until analysis. The concentrations of PBZ and OXPBZ residues in the biological fluid and tissue samples collected at slaughter were measured with the two validated LC-MS/MS methods using deuterated internal standards. The results demonstrate that the validated methods are fit for studying the depletion kinetics of PBZ residues in equine tissues and biological fluids.